Acupuncture-Moxibustion Combined with Rehabilitation Training Is Conducive to Improving the Curative Effect, Cognitive Function, and Daily Activities of Patients with Cerebral Infarction. (21st May 2022) - Zhang, Ding; Huang, Liemi; Zhang, Lun; Gui, Xinghua; Tao, Jiping; Zeng, Pengli; Ding, Min
Abstract : Objective . To elucidate the effect of acupuncture-moxibustion combined with rehabilitation training (RHT) on the curative effect, cognitive function (CF), and activities of daily living (ADL) of patients with cerebral infarction (CI). Methods . This study enrolled 150 patients with CI admitted to the Wuhan Sixth Hospital, Affiliated Hospital of Jianghan University from June 2020 to July 2021. Among them, 80 patients who were treated with acupuncture-moxibustion combined with RHT were included in the research group, and 70 patients who received acupuncture-moxibustion alone were included in the control group. The efficacy, CF, and ADL were observed in both groups, and the influences of the two therapies on serum uric acid (UA), high-sensitivity C-reactive protein (hs-CRP), and cystatin C (Cys-C) were compared. Among the various indexes, the CF of patients was assessed by the Montreal Cognitive Assessment (MoCA), and the ADL was evaluated by the Barthel index. Results . After treatment, the research group presented significantly better efficacy, CF, and ADL than the control group, with lower levels of serum UA, hs-CRP, and Cys-C than the control group and before treatment. Conclusion . Acupuncture-moxibustion combined with RHT can inhibit serum UA, hs-CRP, and Cys-C levels of patients with CI while improving the curative effect, CF, and ADL, which is worthy of clinical promotion.